Appropriate feeding practice and associated factors among under-five children with diarrheal disease in sub-Saharan Africa: a multi-country analysis - Yigizie Yeshaw; Adugnaw Zeleke Alem; Hiwotie Getaneh Ayalew; Alemneh Mekuriaw Liyew; Zemenu Tadesse Tessema; Misganaw Gebrie Worku; Getayeneh Antehunegn Tesema; Tesfa Sewunet Alamneh; Achamyeleh Birhanu Teshale (Tropical Medicine and Health, 2023)
Abstract Background Diarrheal disease is one of the leading causes of child mortality and morbidity in low-income countries. Although the provision of more fluid and solid foods during diarrhea are important to treat the diseases, in Africa, food and fluid restrictions are common during diarrheal illness. Therefore, the aim of this study was to determine appropriate feeding practice and associated factors among under-five children with diarrheal disease in sub-Saharan Africa (SSA). Methods We have used the appended most recent demographic and health survey (DHS) datasets of 35 sub-Saharan countries conducted from 2010 to 2020. A total weighted sample of 42,882 living children with diarrhea were included in the analyses. Multivariable multilevel binary logistic regression was used to identify factors associated with appropriate child feeding practice in SSA. A p value of ≤ 0.05 was used as a cut of point to declare statistically significant variables. Results The overall prevalence of appropriate child feeding practice in this study was 10.45% (95% CI 10.17–10.74). The odds of having appropriate child feeding practice was higher among women with primary (AOR = 1.27: 1.17–1.37), secondary (AOR = 1.38: 1.25–1.52), and higher education level (AOR = 1.52: 1.21–1.90), media exposure (AOR = 1.11: 1.11–1.29), richer (AOR = 1.23:1.01–1.26) and richest (AOR = 1.19:1.05–1.35) wealth index, and currently working (AOR = 1.12: 1.04–1.19). Conclusion The prevalence of appropriate child feeding practice in this study was found to be very low. It advisable to reduce diarrhea-related child mortality through enhancing diarrhea management practice especially by working on the after mentioned factors.